Missed diagnosis of a gallstone ileus: an incomplete laparoscopy due to a putative ventriculoperitoneal shunt infection. (5th April 2013) - Däster, Silvio; Nebiker, Christian A; Hohmann, Joachim; Droeser, Raoul A
Abstract : A 90-year-old woman presented with abdominal pain and vomiting. Initial investigations revealed diffuse abdominal tenderness and fever, combined with leucocytosis and marked elevation of C reactive protein levels. Abdominal CT demonstrated segmental bowel wall thickening in the jejunum near the tip of a ventriculoperitoneal (VP) shunt, which had been placed 17 years before because of hydrocephalus. Pneumobilia was present but no ectopic gallstone was detected at the initial analysis and there were no signs of mechanical ileus. Immediate laparoscopy was performed to exclude small bowel ischaemia. Owing to purulent ascites the VP shunt was externalised, supposing VP shunt infection with reactive jejunitis to be the main problem. Antibiotic treatment was then administered and the remaining part of the shunt was removed 6 days later. However, clinical signs of intestinal obstruction have been aggravated. Therefore, a laparoscopy was repeated 3 days later and a gallstone ileus was diagnosed. After enterolithotomy through a minilaparotomy, the patient was fully recovered.